2016
DOI: 10.1021/acs.macromol.6b00842
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Structural Characterization of Module-Assembled Amphiphilic Conetwork Gels

Abstract: Structural analysis of inhomogeneity-free poly(ethylene glycol)− poly(dimethylsiloxane) (PEG−PDMS) amphiphilic conetwork gels has been performed by the complementary use of small-angle X-ray and neutron scattering. Because of the hydrophobicity of PDMS units, the PEG−PDMS gels exhibit a microphase-separated structure in water. Depending on the volume fraction of PDMS, the microphase-separated structure varies from core−shell to lamellar. The obtained X-ray and neutron scattering profiles are reproduced well us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 51 publications
(75 reference statements)
0
51
0
Order By: Relevance
“…In four of the APCNs, the molar ratio of the hydrophobic MMA to the hydrophilic DMAEMA units in the arms of the stars was fixed at 3–1, with the overall (nominal) degrees of polymerization (DP) of the arms being 10, 20, 30 and 40. This particular composition is expected to result in materials less swollen in water, leading to better‐ordered aqueous nanophases . The remaining two APCNs comprised star block copolymers whose arms were less hydrophobic, with MMA to DMAEMA molar ratios of 1–1, and 1–3, and constant overall (nominal) arm DP equal to 20.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In four of the APCNs, the molar ratio of the hydrophobic MMA to the hydrophilic DMAEMA units in the arms of the stars was fixed at 3–1, with the overall (nominal) degrees of polymerization (DP) of the arms being 10, 20, 30 and 40. This particular composition is expected to result in materials less swollen in water, leading to better‐ordered aqueous nanophases . The remaining two APCNs comprised star block copolymers whose arms were less hydrophobic, with MMA to DMAEMA molar ratios of 1–1, and 1–3, and constant overall (nominal) arm DP equal to 20.…”
Section: Resultsmentioning
confidence: 99%
“…The more compact nature and the usually large molecular weight of star polymers are expected to introduce fewer network defects related to chain entanglements, and, therefore, allow for more regular organization of the nanophases in the phase separated state. Although most of the APCNs already prepared from amphiphilic star block copolymers presented nanophase separation with only short‐range order, some recent reports revealed morphologies with longer‐range order . In these latter reports, a rather low amount of cross‐linker was used, so as to allow more freedom to the polymer segments to reach a lowest‐energy configuration, resulting in the formation of better‐ordered morphologies within the APCNs.…”
Section: Introductionmentioning
confidence: 99%
“…This is usually fulfilled for networks with two hydrophobic components as presented here. In case of amphiphilic conetworks, potential solubility and phase‐separation issues must be considered, but previous work has shown that this is not necessarily a problem . Finding a common solvent is likely easier than overcoming the problem of a stronger incompatibility in the melt.…”
Section: Discussionmentioning
confidence: 99%
“…As an important example, Sakai et al introduced a new type of model network designated as tetra‐PEG gel, which is obtained by heterocomplementary coupling of two orthogonally functionalized tetrahedron‐like polyethylene glycol (PEG) macromonomers (A 4 + B 4 ). The approach was later extended to hybrid gels . Such gels are characterized by their homogeneous structure and resultant high mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…By playing with the degree of cross‐linking, p , controlled‐defect networks are prepared with which percolation problems can be revisited . Furthermore, by introducing hetero‐co‐prepolymers, various types of novel gels (networks) have been developed, such as non‐swellable implantable gels, very tough “fuse”‐link gels, and amphiphilic conetworks . Furthermore, model polyelectrolyte gels, in which the concentration and spatial distribution of charges are precisely controlled, are now available .…”
Section: Discussionmentioning
confidence: 99%